ANALISIS KESIAPAN PEMBUDIDAYA KJA DAN PEMBENIH HSRT KOMODITAS IKAN KERAPU DALAM MENGHADAPI PERDAGANGAN BEBAS DENGAN PENDEKATAN THEORY OF PLANNED BEHAVIOR - Nanda Widaninggar; Hamzah Fansuri Yusuf (UNEJ e-Proceeding)
The study aimed to analyze and review Test factors affecting the intention to review the readiness to behave hearts Facing Free Trade Commodities ON WITH Groupers using Theory of Planned Behavior. The entire study population cultivators BY KJA And pembenih HSRT in Situbondo, East Java Province Singers, conducted quantitative Operates, WITH spread questionnaires, using Method of Structural Equation Modelling population of 114 farmers Fishermen KJA And pembenih HSRT, distributed questionnaires a total of 70 copies, And The Back And can be processed a number of 43 copies. Based WITH analysis using SEM, TIN findings that affect human constructs against perceived behavioral control, subjective Against influential technology norms, and Commitment Marine and Fisheries Agency Against Third influential NOT IN readiness intervention variable hearts Facing Free Trade. While constructs Regulation Against the influence of perceived control of behavior and attitudes affect the resistance against directions. The only constructs The influential Against three hearts IN readiness Facing Free Trade Financing Is a Formal Financial Institutions. Highest rated affecting intention hearts Readiness Facing Free Trade Is a Subjective Norm.